MODEL FOR DEVELOPING THE COGNITIVE ACTIVITY OF FUTURE TEACHERS IN THE CONTEXT OF INNOVATIVE EDUCATION - Ulasheva Nafisa Himmat qizi (Modern American Journals, 2026)
This article examines a model for developing the cognitive activity of future teachers in the context of innovative education. The study analyzes modern pedagogical technologies, interactive teaching methods, and the potential of the digital learning environment in enhancing students’ cognitive engagement. The structural components, implementation stages, and effectiveness criteria of the proposed model are substantiated, focusing on fostering independent thinking, analytical skills, and reflective competencies in prospective teachers.
Keywords: Innovative education, cognitive activity, pedagogical model, future teacher, cognitive development, competency-based approach, interactive methods, digital learning environment